Clinical Characteristics and Neurologic Outcomes of X-Linked Myotubular Myopathy - Hyewon Woo; Seungbok Lee; Ji Yeon Han; Woo Joong Kim; Man Jin Kim; Moon-Woo Seong; Soo Yeon Kim; Anna Cho; Byung Chan Lim; Ki Joong Kim; Jong-Hee Chae (Korean Child Neurology Society, 2022)
Purpose X-linked myotubular myopathy (XLMTM) is a rare condition of centronuclear myopathy caused by myotubularin 1 (MTM1) mutations. Patients with XLMTM show different neurodevelopmental outcomes after the neonatal period depending on age and acquired hypoxic damage. We aim to evaluate the clinical characteristics and neurodevelopmental outcomes of patients with XLMTM who were followed up at a single center. It is essential to understand the volume and conditions to prepare for being a candidate for new therapeutic strategies. Methods Patients diagnosed with centronuclear myopathy by muscle pathology and MTM1 mutation analysis were included. We retrospectively investigated motor milestones, communication skills, and bulbar and respiratory function in the patients. The patients were categorized into two groups: with and without hypoxic insults (HI). Results All 13 patients were severely affected by neonatal hypotonia and required respiratory support and a feeding tube during the neonatal period. The follow-up duration was 4.4 years (range, 0.3 to 8.9). In the non-HI group, developmental milestones were delayed but were slowly achieved. Some patients underwent training in oral feeding with thickened foods and weaning from ventilation. Patients with HI showed poor motor function catch-up and communication skills. Three deaths were associated with acute respiratory failure. Conclusion Patients with XLMTM without HI can survive long-term with the slow achievement of motor milestones and bulbar and respiratory function. However, hypoxic brain damage following acute respiratory failure negatively influences their developmental potential or even lead to death. Therefore, parental education for proper respiratory management is necessary, especially for young children.